Implementasi Pengelolaan Limbah Cair Rumah Sakit Islam Ibnu Sina Pekanbaru - Hartati Hartati; Adrianto Ahmad; Elda Nazriati (Universitas Riau, 2015)
Liquid waste discharged from Ibnu Sina Muslim Hospital have a negative impacton the environment if the waste is not properly managed. Therefore it is mandatory to controlthe disposal priar to discharging in to the environtment. The present study aimed to determineliquid waste magement by determining the quality of effluent of Ibnu Sina Muslim Hospitaland comparing to the liquid waste quality standard of the minister of environment (Decre No58/1995) on the liquid waste quality of hospital activities. Data obtained by observation,questionnaires and laboratotory examination. Apparently, the temperatur BOD5, COD, pHana MPN meets effluent quality standard; while the ammonia, phosphate and TSS exceededthe upper treshold. Wastewater management Ibnu Sina Muslim as chlorine tank. Knowledgeof employees and health workers Ibnu Sina Muslim Hospital Pekanbaru on liquid wastemanagement has been high but in the setting process and operating conditions ware less.